1988
DOI: 10.1177/00220345880670050401
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Caries around Restorations in Roots

Abstract: An artificial caries technique was used to produce caries-like lesions in the cavity walls adjacent to microfilled resin restorations with and without dentin bonding agent, and glass-ionomer cement restorations, in the roots of extracted teeth. The lesions had histological characteristics similar to those of natural lesions and to those of the lesions produced by other experimental methods. The zonal pattern of the lesions was examined by means of polarized light microscopy and microradiography, and the depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
3

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
2
15
0
3
Order By: Relevance
“…The present findings agree with Ten Cate 24) (1990), who stated that enamel remineralizaand Purton & Rodda 21) in studies using polarized light microscopy which revealed formation of mild demineralization and that the establishment and progression of demineralization in these cases was reduced, possibly due to the precipitation of calcium and phosphate triggered by the high fluoride release of these materials. This may be explained by the intensive fluoride release of this material, which depends on its concentration in the material and especially on the presence of ionic fluoride, which enhances its release.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present findings agree with Ten Cate 24) (1990), who stated that enamel remineralizaand Purton & Rodda 21) in studies using polarized light microscopy which revealed formation of mild demineralization and that the establishment and progression of demineralization in these cases was reduced, possibly due to the precipitation of calcium and phosphate triggered by the high fluoride release of these materials. This may be explained by the intensive fluoride release of this material, which depends on its concentration in the material and especially on the presence of ionic fluoride, which enhances its release.…”
Section: Discussionsupporting
confidence: 92%
“…Since it represented the control group, its performance is in agreement with the findings of Purton and Rodda 21) , who observed that non-fluoridated composite resins do not present any potential to inhibit demineralization.…”
Section: Discussionsupporting
confidence: 88%
“…It seems that caries inhibition in the root surface was controlled by transport of fluoride ions released from the restoration surface into the storage medium and then into the tooth surface, and was not influenced by the ability of fluoride to penetrate the adhesive layer in the current model. 21 In the clinical situation, fluoride may become concentrated in plaque and may therefore have a more beneficial surface effect.…”
Section: Discussionmentioning
confidence: 99%
“…In 1988, Purton and Rodda 15 showed that the cement released not only fluoride ions, but also calcium and phosphate, into the tooth structure. This was subsequently confirmed by ten Cate and van Duinen in 1995 16 and eventually, by Ngo et al 17 This last group conducted a clinical experiment using a newer material in which strontium had been substituted for calcium, in order to make the cement radiopaque.…”
mentioning
confidence: 99%